Urban space maintainability factors based on life cycle approach - Rathnasiri, Nimali Erandathi; De Silva, Nayanthara; Wijesundara, Janaka (Facilities (Bradford, West Yorkshire, England), 2024)
Purpose The maintainability of urban spaces has become critical with rapid urbanization to create an effective and safe environment for the increasing population. The absence of scientific studies exploring the factors that affect urban space maintainability (USM) has hindered the incorporation of maintainability aspects during the urban space planning and designing stages. This paper aims to establish critical factors for USM. Design/methodology/approach Qualitative content analysis is performed under an abductive approach to developing USM factors. A bibliometric search is conducted using databases including Scopus Elsevier, Emerald Insight, Science Direct, IEEE XPLORE and the American Society of Civil Engineers. The selected primary data set comprises journal papers on USM published after 2000. Seventy-three journal articles are selected through a comprehensive screening procedure and subjected to further analysis. The literature findings are processed via a software-assisted systematic coding and visualizing of the key data using NVivo 12 software. The coded USM factors are validated based on experts’ consensus statements by conducting an expert focus group discussion. Findings Twelve critical factors are established for USM; they include six design stage-related factors, one construction stage-related factor and five operational stage-related factors. Research limitations/implications Established USM factors give an insight into the main focus areas when incorporating maintainability into urban spaces. Originality/value The authors establish a set of maintainability factors for urban spaces based on the life cycle stages. USM factors such as vegetation management, interdepartmental coordination and work zone safety draw attention to context-specific aspects of USM.